FT-ICR: a non-destructive detection for on-line mass measurements at SHIPTRAP - Weber, Christine; Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
The SHIPTRAP facility is set up behind the velocity filter SHIP at GSI. One of the main physics goals is the direct mass determination of trans-uranium nuclides by Penning trap mass spectrometry. In this contribution the applicability of the non-destructive Fourier Transform-Ion Cyclotron Resonance (FT-ICR) detection technique to mass spectrometry of short-lived nuclides is discussed.
Gesehen am 28.02.2020